PERAN HOOLIGAN FISIP SEBAGAI KELOMPOK SUPPORTER UNIVERSITAS JENDERAL SOEDIRMAN - Putri, Rizqi Wulandari; Saputra, Diki; Harmadhani, Abiyoso; Restiawan, Ilham Rizky; Novianti, Wiwik (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2024)
This research aims to describe and view the behavior of This study aims to describe and see the behavior of how the FISIP Hooligan social group forms each of its members as part of the group itself to process the participation agenda of the FISIP Hooligan group itself. In addition to the FISIP Hooligans group who move as football supporters, on the other hand this group can become a campus community with its group agenda. Therefore, intense interaction can shape group values in the form of solidarity, culture and loyalty which can support the internal progress of the group to be able to show its identity externally. The FISIP Hooligans Group serves as a forum for information, both about discussions, lecture materials or other things that provide their own experiences for each member.